2015
DOI: 10.1128/jcm.00165-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ebola Virus Inactivation Procedures for Plasmodium falciparum Malaria Diagnostics

Abstract: c Plasmodium falciparum malaria is highly endemic in the three most affected countries in the current epidemic of Ebola virus disease (EVD) in West Africa. As EVD and malaria are clinically indistinguishable, both remain part of the differential diagnosis of ill travelers from returning from areas of EVD transmission. We compared the performances of a rapid diagnostic test (Binax-NOW) and real-time PCR with P. falciparum-positive specimens before and after heat and Triton X-100 inactivation, and we documented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Additionally, the dual treatment method is relatively quick, with inactivation being achievable within 30 min, which helps with throughput of samples. The heating time is reduced compared to previous methods (8)(9)(10). After inactivation, samples are then able to be manipulated outside containment, which increases sample throughput.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Additionally, the dual treatment method is relatively quick, with inactivation being achievable within 30 min, which helps with throughput of samples. The heating time is reduced compared to previous methods (8)(9)(10). After inactivation, samples are then able to be manipulated outside containment, which increases sample throughput.…”
Section: Discussionmentioning
confidence: 69%
“…The CDC recommends Triton X-100 and heat treatment for 1 h for diagnostic samples containing hemorrhagic fever viruses (8), and this method has been adopted by many laboratories for handling of samples that may contain EBOV (9). Heating (alone or with acetic acid) for 1 h at 60°C has also been shown to reduce the titer of EBOV (10).…”
Section: A N Outbreak Of Ebola Virus Disease (Evd) Occurred In West Amentioning
confidence: 99%
“…Presently, laboratory EBOV inactivation is accomplished by gamma irradiation (8), UV radiation (9), nanoemulsion (10), and photoinducible alkylating agents (11), but these methods are not applicable in outbreak situations or as bedside inactivation methods. Other EBOV inactivation methods, such as acetic acid (12), heat (12), AVL buffer (13), TRIzol (13) or the combination of heat and Triton X-100 (14), are more applicable in outbreak situations and are currently used in field laboratories. Unfortunately, all of these methods require hands-on handling and manipulation of the sample before EBOV is inactivated.…”
mentioning
confidence: 99%
“…Thus, methanol treatment alone is sufficient for EBOV inactivation and improvement of biosafety. Although not reported in this study, multiple reports have indicated that neither methanol fixation nor heat inactivation will negatively affect the quality of whole-blood thin smears or the diagnosis of malaria during the staining procedures for malaria (8,(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Although it is believed that the additional Triton X-100 would inactivate EBOV particles within malaria samples and that the impact on clinical biochemical and histology assays is minimal (14,16,17), no data have been found in peer-reviewed material to support the use of Triton X-100 in inactivating EBOV.…”
mentioning
confidence: 99%